The preyssler-type polyoxotungstate exhibits anti-quorum sensing, antibiofilm, and antiviral activities - Faleiro, Maria Leonor (2022)
The increase in bacterial resistance to antibiotics has led researchers to find new compounds or find combinations between different compounds with potential antibacterial action and with the ability to prevent the development of antibiotic resistance. Polyoxotungstates (POTs) are inorganic clusters that may fulfill that need, either individually or in combination with antibiotics. Herein, we report the ability of the polyoxotungstates (POTs) with Wells-Dawson P2W18, P2W17, P2W15, and Preyssler P5W30 type structures to differently affect Gram-negative and Gram-positive microorganisms, either susceptible or resistant to antibiotics. The compound P5W30 showed the highest activity against the majority of the tested bacterial strains in comparison with the other tested POTs (P2W15, P2W17 and P2W18) that did not show inhibition zones for the Gram-negative bacteria, A. baumanii I73775, E. coli DSM 1077, E. coli I73194, K. pneumoniae I7092374, and P. aeruginosa C46281). Generally, the results evidenced that Gram-positive bacteria are more susceptible to the POTs tested. The compound P5W30 was the one most active against S. aureus ATCC 6538 and MRSA16, reaching <0.83 mg·mL−1 (100 µM) and 4.96 mg·mL−1 (600 µM), respectively. Moreover, it was verified by NMR spectroscopy that the most promising POT, P5W30, remains intact under all the experimental conditions, after 24 h at 37 ◦C. This prompted us to further evaluate the anti-quorum sensing activity of P5W30 using the biosensor Chromobacterium violaceum CV026, as well as its antibiofilm activity both individually and in combination with the antibiotic cefoxitin against the methicillin-resistant Staphylococcus aureus 16 (MRSA16). P5W30 showed a synergistic antibacterial effect with the antibiotic cefoxitin and chloramphenicol against MRSA16. Moreover, the antibiofilm activity of P5W30 was more pronounced when used individually, in comparison with the combination with the antibioticcefoxitin. Finally, the antiviral activity of P5W30 was tested using the coliphage Qβ, showing a dosedependent response. The maximum inactivation was observed at 750 µM (6.23 mg·mL−1 ). In sum, P5W30 shows anti-quorum sensing and antibiofilm activities besides being a potent antibacterial agent against S. aureus and to exhibit antiviral activities against enteric viruses.